Pengaruh Pendekatan Bermain Terhadap Pembelajaran Atletik Nomor Lari Bagi Tuna Grahita - Lufthansa, Luthfie; Anangga Widya Pradipta; Ary Artanty; Antonius Prasetyo Hadi (Universitas Singaperbangsa Karawang, 2023)
In adaptive physical education learning for the mentally disabled, the most effective way is through playing sports with modifications to the game rules. Games for the mentally retarded are the main form of social learning activity for them. Games for mentally retarded children are activities that create a happier atmosphere which are carried out only to create a greater sense of enjoyment during the activity itself, not also to gain something that is felt through the activity. Where a game that tends to involve a lot of basic movement skills is games. The playing approach used is a chase tom game. Where there is a student who is responsible for running to avoid being caught, and one of the students runs to catch his friend. The type of research carried out was experimental with pretest-posttest treatment and used descriptive methods. The research was conducted at SLNB Kedungkandang, Malang City with the number of research subjects being 7 students with intellectual disabilities. Based on the research results, the asymp sig = 0.041. Because the result of asymp sig = 0.041 < α = 0.06 means learning athletics for running numbers before treatment and after treatment.